The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1088/1054-660x/25/3/035101
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temporal characteristics on the power scalability of the fiber amplifier

Abstract: We have performed an experimental study of the power scaling ability of a fiber amplifier limited by the temporal stability of its seed light. Three seed sources with various temporal characteristics are demonstrated for the fiber amplifier. An accurate model of the fiber amplifier is established by considering the time dynamics of the laser. The results show that the self-pulsation can reduce the SRS threshold of the fiber amplifier and limit the power scalability of the fiber amplifier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Such a result is surprising because it is contradictory to all the theoretical and numerical predictions formerly reported. One possible reason is that the seed power instability become serious with lowering the seed power, which induces the enhancement of SRS [34]. In order to verify this reason, the seed source was improved (i.e., Seed II) as shown in Fig.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…Such a result is surprising because it is contradictory to all the theoretical and numerical predictions formerly reported. One possible reason is that the seed power instability become serious with lowering the seed power, which induces the enhancement of SRS [34]. In order to verify this reason, the seed source was improved (i.e., Seed II) as shown in Fig.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…On the other hand, though the configuration of our system is approximate to that of [26], the bandwidths of the OC FBG in the oscillators are different-0.15 nm and 0.4 nm respectively. Previous works have demonstrated that the oscillator induces stronger temporal fluctuations when using a narrower OC FBG, and the SRS effect and spectral broadening increase quickly with enhanced temporal fluctuations [27][28][29][30][31]. This may explain why the SRS and spectral broadening in our amplifier are more remarkable.…”
Section: Srs Effect With Different Types Of Seed Laser Injectionmentioning
confidence: 62%
“…If the injected power is too low, enhanced ASE will put our amplifier at risk under high-power conditions. According to [27,30,31], SRS is associated with the temporal stability of the seed lasers, so it is also important to adopt temporal stable seed sources to suppress SRS. In our next attempt, one RFL and one PMS (Seed Lasers II and III) are utilized respectively in the same amplifier for comparison.…”
Section: Srs Effect With Different Types Of Seed Laser Injectionmentioning
confidence: 99%
“…The results indicate that the temporal fluctuations of the pulse peak are weak when the FWHM linewidth is larger than 2 nm, but are significantly strengthened when the FWHM linewidth is smaller than 2 nm. Thus, the wideband ns-SFS seed can effectively resolve issues such as self-pulsing commonly observed in oscillator-based fiber seeds [9,10] , while extensive spectral filtering also leads to a degradation in the temporal stability of the ns-SFS seed. Moreover, the average power of the ns-SFS obtained by AOM 1 modulation is 2.3 mW.…”
Section: The Nanosecond Pulsed Superfluorescent Fiber Sourcementioning
confidence: 99%
“…Typically, high-power all-fiberized nanosecond pulsed amplifiers employ a master oscillator power amplifier (MOPA) configuration where the nanosecond fiber seed is achieved via a Q-switched regime or external modulation of a continuouswave fiber laser [7,8] . However, the stochastic self-pulsing and the interactions of longitudinal modes inherent in fiber oscillators degrade their temporal stability and the threshold of the nonlinear effects, thereby limiting the average power and pulse energy of all-fiberized pulsed amplifiers [8][9][10] . In addition, all-fiberized nanosecond pulsed amplifiers with low coherence are demanded in the high-quality full-field imaging of dynamic targets on the nanosecond timescale and in other applications [11] .…”
Section: Introductionmentioning
confidence: 99%